Neural Correlates of Speed-Tuned Motion Perception in Healthy Adults. (June 2018) - Meier, Kimberly; Partanen, Marita; Giaschi, Deborah
It has been suggested that slow and medium-to-fast speeds of motion may be processed by at least partially separate mechanisms. The purpose of this study was to establish the cortical areas activated during motion-defined form and global motion tasks as a function of speed, using functional magnetic resonance imaging. Participants performed discrimination tasks with random dot stimuli at high coherence, at coherence near their own thresholds, and for random motion. Stimuli were moving at 0.1 or 5 deg/s. In the motion-defined form task, lateral occipital complex, V5/MT+ and intraparietal sulcus showed greater activation by high or near-threshold coherence than by random motion stimuli; V5/MT+ and intraparietal sulcus demonstrated greater activation for 5 than 0.1 deg/s dot motion. In the global motion task, only high coherence stimuli elicited significant activation over random motion; this activation was primarily in nonclassical motion areas. V5/MT+ was active for all motion conditions and showed similar activation for coherent and random motion. No regions demonstrated speed-tuning effects for global motion. These results suggest that similar cortical systems are activated by slow- and medium-speed stimuli during these tasks in healthy adults.